Unraveling the genetics of otitis media: from mouse to human and back again. - Rye, MS; Bhutta, M; Cheeseman, M; Burgner, D; Blackwell, J; Brown, S; Jamieson, SE (2011)
Otitis media (OM) is among the most common illnesses of early childhood, characterised by the presence of inflammation in the middle ear cavity. Acute OM and chronic OM with effusion (COME) affect the majority of children by school age and have heritability estimates of 40-70%. However, the majority of genes underlying this susceptibility are, as yet, unidentified. One method of identifying genes and pathways that may contribute to OM susceptibility is to look at mouse mutants displaying a comparable phenotype. Single-gene mouse mutants with OM have identified a number of genes, namely, Eya4, Tlr4, p73, MyD88, Fas, E2f4, Plg, Fbxo11, and Evi1, as potential and biologically relevant candidates for human disease. Recent studies suggest that this "mouse-to-human" approach is likely to yield relevant data, with significant associations reported between polymorphisms at the FBXO11, TLR4, and PAI1 genes and disease in humans. An association between TP73 and chronic rhinosinusitis has also been reported. In addition, the biobanks of available mouse mutants provide a powerful resource for functional studies of loci identified by future genome-wide association studies of OM in humans. Mouse models of OM therefore are an important component of current approaches attempting to understand the complex genetic susceptibility to OM in humans, and which aim to facilitate the development of preventative and therapeutic interventions for this important and common disease.